Foucault’s resistance to biopolitics - Karaboue, Michele Ahmed Antonio (Progress in Nutrition, 2024)
One of the most topical issues in bioethics is the concept of medicalization. In order to deal with this issue, it is impossible to ignore Michel Foucault’s analysis of the subject. The French philosopher is a reference point for all those attempting to reflect on and undertake research into this field. Foucault’s importance in this topic lies in his having traced the structural trajectory with which to understand the very construction of medicalization. In particular, he understands medicalization not as a phenomenon that springs from other situations but as a framework of meaning to understand human phenomena. Its ascent begins the moment medicine becomes social, when it starts to concern an ever-increasing range of issues, so leading to an absolutization of health which is nothing more than a normative way of understanding specific vital parameters. This expansion includes the growing focus on nutrition and dietary habits as essential components of health. The medicalization of nutrition reflects a shift where diet is no longer seen merely as a personal or cultural practice but is instead framed as a medical and moral obligation, subject to scientific scrutiny and public policy. Such a perspective transforms food choices into health choices, governed by medical guidelines that dictate what is considered a ’healthy’ diet. This shift loses all reference to regulations, thus becoming the key to grasping the naturalness of man, which at the same time allows human existence to be normalized. For this reason, medicine becomes the instrument of a technique of power – biopolitics – which, by acting on the discipline of the individual to secure the population and achieve regulation over it, so dominates life entirely. Through the lens of nutritional medicalization, food becomes a tool of biopolitical control, where public health initiatives aim to shape behaviors and norms, ultimately extending the reach of medicalization into everyday life.